Media Representations of Adolescent Pregnancy: The Problem with Choice - Shaw, Anita (Atlantis, 2010)
Although teenage pregnancy has become more socially acceptable than in the past, pregnant teenagers continue to be stigmatized. This paper examines some of the ways in which two widely circulated media representations of adolescent pregnancy, Papa Don't Preach and Juno, both challenge and perpetuate the stigma.